Outcome after ablation in patients with low-risk thyroid cancer (ESTIMABL1): 5-year follow-up results of a randomised, phase 3, equivalence trial. Issue 8 (August 2018) - Schlumberger, Martin; Leboulleux, Sophie; Catargi, Bogdan; Deandreis, Desiree; Zerdoud, Slimane; Bardet, Stephane; Rusu, Daniela; Godbert, Yann; Buffet, Camille; Schvartz, Claire; Vera, Pierre; Morel, Olivier; et al.
Summary: Background: In ESTIMABL1, a randomised phase 3 trial of radioactive iodine ( 131 I) administration after complete surgical resection in patients with low-risk thyroid cancer, 92% of patients had complete thyroid ablation at 6–10 months, defined as a recombinant human thyroid-stimulating hormone (rhTSH)-stimulated serum thyroglobulin concentration of 1 ng/mL or less and normal findings on neck ultrasonography. Equivalence was shown between low-activity (1·1 GBq) and high-activity (3·7 GBq) radioactive iodine and also between the use of rhTSH injections and thyroid hormone withdrawal. Here, we report outcomes after 5 years of follow-up. Methods: This multicentre, randomised, open-label, equivalence trial was done at 24 centres in France. Between March 28, 2007, and Feb 25, 2010, we randomly assigned (1:1:1:1) adults with low-risk differentiated thyroid carcinoma who had undergone total thyroidectomy to one of four strategies, each combining one of two methods of thyrotropin stimulation (rhTSH or thyroid hormone withdrawal) and one of two radioactive iodine activities (1·1 GBq or 3·7 GBq). Randomisation was by computer-generated sequence, with variable block size. Follow-up consisted of a yearly serum thyroglobulin measurement on levothyroxine treatment. Measurement of rhTSH-stimulated thyroglobulin and neck ultrasonography were done at the discretion of the treating physician. No evidence of disease was defined as serum thyroglobulin of 1 ng/mL or less on levothyroxine treatment and normal results on neck ultrasonography, when performed. This study was registered withClinicalTrials.gov, numberNCT00435851 . Findings: 726 patients (97% of the 752 patients originally randomised) were followed up. At a median follow-up since randomisation of 5·4 years (range 0·5–9·2), 715 (98%) had no evidence of disease. The other 11 had either structural disease (n=4), raised serum thyroglobulin concentration (n=5), or indeterminate findings on neck ultrasonography (n=2). At ablation, six of these patients had received 1·1 GBq radioactive iodine (five after rhTSH and one after withdrawal) and five had received 3·7 GBq (two after rhTSH and three after withdrawal). TSH-stimulated (either after rhTSH injections or thyroid hormone withdrawal according to the treatment group) thyroglobulin concentration measured at the time of ablation was prognostic for structural disease status at ablation, ablation status at 6–10 months, and the final outcome. Interpretation: Our findings suggest that disease recurrence was not related to the strategy used for ablation. These data validate the use of 1·1 GBq radioactive iodine after rhTSH for postoperative ablation in patients with low-risk thyroid cancer. Funding: French National Cancer Institute (INCa), French Ministry of Health, and Sanofi Genzyme.